Kompetensi Pedagogik Guru Seni Budaya Dalam Meningkatkan Kreativitas Peserta Didik - Yayan Nuryana (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This thesis is entitled: Cultural Arts Teacher Pedagogic Competence in Improving Student Creativity (Descriptive Study at SMK Negeri 3 Tasikmalaya City). Arts and culture teachers are responsible for providing effective, inspiring and supportive learning towards the development of students' creativity. through good pedagogical competence, arts and culture teachers can become effective agents of change in creating a learning environment that inspires, empowers, and promotes the diversity of cultural arts expressions in society. This study aims to determine the pedagogical competence of arts and culture teachers in planning, implementing and evaluating learning, the steps taken, the obstacles encountered, and the solutions made in increasing the creativity of students at SMK Negeri 3 Tasikmalaya City. Data collection was carried out through observation, interviews, and documentation studies with the steps of data collection, data reduction, data presentation, and drawing conclusions. The validity of the data was carried out through triangulation with data sources from school supervisors, school principals, arts and culture teachers, visual communication design teachers, leather and imitation DPK teachers, wood and rattan DPK teachers, school committees and student representatives. From the results of the study it can be concluded that: (1) The pedagogical competence of arts and culture teachers at SMK Negeri 3 Tasikmalaya in planning, implementing and evaluating learning is quite good. (2) The steps taken are to observe the opportunities that exist, foster curiosity, create fun learning, integrate technology, open a wide network, encourage students to always dare to try something new, think positively, be confident, develop extra-curricular activities and take part in various events. (3) Obstacles faced are students' lack of understanding of the goals to be achieved, fear of making mistakes, fear of being criticized, not thinking pro-actively, problems with school financial funding, lack of participation from parents, infrastructure and availability of practicum materials that are not optimal. (4) Efforts made in dealing with these obstacles are to provide understanding to students, build mentality and encourage them to always think critically, unify understanding of the importance of extra-curricular activities in schools, and submit complete infrastructure facilities that are not yet optimal. Based on these conclusions, it is suggested: (1) Schools must be able to make a comprehensive and realistic School Financial Budget Plan, by prioritizing clear priority scales for effective and efficient allocation of funds, (2) In the learning process it is hoped that the teacher will provide material according to the needs them, open assignments that challenge them to always think critically, creatively, collaboratively and innovatively, (3) students are expected to continue to practice, be confident, not afraid of making mistakes and always ask for suggestions and input from the teacher to produce quality work.